1997
DOI: 10.1111/j.1432-1033.1997.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet‐B‐Radiation‐Induced Changes in Nicotinamide and Glutathione Metabolism and Gene Expression in Plants

Abstract: Pea (Pisum sativum L. cv. Greenfeast) plants were exposed to supplementary ultraviolet‐B (UV‐B) radiation (biologically effective dose rates normalised to 300 nm, UV‐BBE300: 0.18, 0.32 or 1.4 W m−2). Leaf nicotinamide, trigonelline, GSHtot (total glutathione) and GSSG (oxidised glutathione) levels remained unchanged after exposure to the lowest dose rates. 1.4 W m−2 UV‐BBE,300: gave rise to 60‐fold and 4.5‐fold increases in GSSG and GSHtot, respectively. 3.5‐fold and 9.5‐fold increases were found in nicotinami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 43 publications
2
40
1
Order By: Relevance
“…Recently, Wagner et al [20] concluded that both genes probably have overlapping functions, and both are required to act synergistically to establish pyridoxine homeostasis. Also, comparable basal levels of vitamin B 6 were detected in both the pdx1.3 mutant and in the Col-0 ecotype. After exposure to UV-B, significantly increased vitamin B 6 levels were found in Col-0 wild type (Fig.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Recently, Wagner et al [20] concluded that both genes probably have overlapping functions, and both are required to act synergistically to establish pyridoxine homeostasis. Also, comparable basal levels of vitamin B 6 were detected in both the pdx1.3 mutant and in the Col-0 ecotype. After exposure to UV-B, significantly increased vitamin B 6 levels were found in Col-0 wild type (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Increased activities of anti-oxidative enzymes have been demonstrated, in addition to decreased content of antioxidants [6]. Also, changes in expression of ROS-dependent genes, such as PR-1 and PR-5, indicate that ROS is involved in at least high level or long-term UV-B responses [7,32,34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants respond to UV-B stress by activating antioxidant enzymes like Superoxide dismutase, Ascorbic acid peroxidase, Glutathione reductase (Takeuchi et al 1995;Rao et al 1996;Teckchandani and Guruprasad 1998;Jain et al 2003;Kataria et al 2007). Plants also respond to UV-B by enhancing the endogenous level of ascorbic acid (Rao et al 1996;Sharma et al 1998;Jain et al 2004a, b) and glutathione (Takeuchi et al 1996;Kalbin et al 1997). In addition to this synthesis of UV absorbing substances like flavonoids and other phenolic compounds are enhanced in response to supplemental UV-B (Searles et al 2001;Day and Neale 2002).…”
Section: Introductionmentioning
confidence: 99%